2006
DOI: 10.1097/01.shk.0000187982.56030.94
|View full text |Cite
|
Sign up to set email alerts
|

Immune Effects of Resuscitation With Hboc-201, a Hemoglobin-Based Oxygen Carrier, in Swine With Moderately Severe Hemorrhagic Shock From Controlled Hemorrhage

Abstract: HBOC-201, a hemoglobin-based oxygen carrier, improved physiologic parameters and survival in hemorrhagic shock (HS) animal models. However, resuscitation from HS and the properties of different fluids influence immune responses. The aim of this study was to determine if HBOC-201 significantly alters immune function in traumatic HS. Anesthetized pigs underwent soft tissue injury, controlled hemorrhage of 40% of blood volume, and resuscitation with HBOC-201 or Hextend, or no resuscitation. Sequential whole-blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
(30 reference statements)
6
19
0
2
Order By: Relevance
“…To the contrary, it may help to attenuate the existing inflammatory symptom. Similar results were also seen in a swine model of HBOC-201, which showed that HBOC-201 had no significant adverse or beneficial effects on immune function in a swine model of moderately severe HS and severe controlled HS [14][15][16]. Our in vitro results are consistent with in vivo results in that there is no inflammatory reaction caused by addition or infusion of pPolyHb.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To the contrary, it may help to attenuate the existing inflammatory symptom. Similar results were also seen in a swine model of HBOC-201, which showed that HBOC-201 had no significant adverse or beneficial effects on immune function in a swine model of moderately severe HS and severe controlled HS [14][15][16]. Our in vitro results are consistent with in vivo results in that there is no inflammatory reaction caused by addition or infusion of pPolyHb.…”
Section: Discussionsupporting
confidence: 81%
“…Ortegon et al observed that HBOC-201 had immune-activating potential, especially enhancement of neutrophilic β 2 integrin (CD11b) expression at high concentration in vitro [13]. However, in vivo in moderate and severe controlled hemorrhagic shock (HS) in swine, with the exception of mildly increased plasma levels of the anti-inflammatory Th-2 cytokine, IL-10, HBOC-201 had minimal effects on innate immune responses [14][15][16]. As well, in trauma patients human polymerized hemoglobin (Polyheme) diminished immune activation in comparison with blood transfusions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Em alguns estudos esse composto demonstrou atividade imunomodulatória, diminuindo a migração e o acúmulo de neutrófilos no tecido pulmonar, além de apresentar baixo potencial imunogênico e inflamatório [Masuno et al 2005, Dong et al 2006. Em modelos animais, demonstrou atividade vasoconstritora e aumento da PAM mais efetivo que a obtida tanto com cristalóides quanto com colóides isotônicos [Boura et al 2003, Knudson et al 2003], porém seu uso ainda carece de estudos em humanos.…”
Section: Alternativas à Reposição Volêmica Tradicionalunclassified
“…Em estudo publicado há pouco, não foi observado efeito no sistema imune decorrente da infusão de carreador de oxigênio livre de células baseado em Hb. 112 …”
Section: -111unclassified